Government discretionary transfers and overinsurance - Forteza, Alvaro (Estudios de Economía, 2016)
Excess distortions in government transfer policies might result from the government lack of ability to commit not to help unlucky agents. Incentive considerations that are crucial in standard insurance in the presence of moral hazard play, no role in this case. A benevolent government that sets transfers after agents have chosen their effort faces a pure risk-sharing problem and provides full insurance, inducing too little effort. The lack of commitment ability might also cause indeterminacy: the economy might end in any of several equilibria, without the government being able to push it to a particular one.